THE ROLE OF AUDIT COMMITTEE IN MODERATING THE EFFECT OF EARNINGS MANAGEMENT AND TAX AVOIDANCE ON COMPANY VALUE - Nurdiniah, Dade; Diyani, Lucia Ari (School of Accountancy, University of Agung Podomoro, 2022)
This study aims to determine the role of audit committee in moderating the impact of profitmanagement and tax avoidance on the value of the business. The population of this study is allmanufacturing companies listed on the Indonesian Stock Exchange, while thee research sample is ofmanufacturing company data, obtains on the Indonesian Stock Exchange in 2015-2019. The sampleselection technique used does not affect, the number of obtains on samples was 28 and the number ofobservations of research data obtain affect. This study used multiple linear regression and moderateregression analysis with a Random Effects Model approach. The findings of this. The study indicatesthat earnings management has a negative effect on firm value, while tax avoidance as proxies studyindicates effective managements no effect on firm value. Then the audit committee does not moderatethe effect of earnings management on firm value, as well as the audit committee does not moderate theeffect of tax avoidance on firm value.